2020
DOI: 10.3846/jau.2019.6584
|View full text |Cite
|
Sign up to set email alerts
|

Space Configuration as an Adaptation Element of Madurese Migrant Urban Settlements in Malang

Abstract: Humans interacting with their physical and social environments always try to adapt individually or in groups. In the adaptation process, a space dynamic will occur and cause space changes. Adaptation elements include the physical environment, socio-cultural environment, and behavior. Interaction among the adaptation elements will form changes to space configuration. Kotalama is the largest Madurese migrant settlement in Malang and was established in the 1950s. Research on space configuration was conducted to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Finally, the study of social production and consumption of space can also pave the way for how architecture as discipline can contribute for social and humanity studies. Through architecture, we can read the urban process, where the spaces represents citizens struggle (Chaudhary, 2020), dwelling adaptation (Asikin et al, 2019, and social order reconfiguration (Sassen, 2010). If design is viewed as means of human desire to reach better future (Dovey, 2010), the practice of architecture can be put to shape, condition, and facilitate social relation and to transmit social meaning for good built forms (Yaneva, 2008(Yaneva, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the study of social production and consumption of space can also pave the way for how architecture as discipline can contribute for social and humanity studies. Through architecture, we can read the urban process, where the spaces represents citizens struggle (Chaudhary, 2020), dwelling adaptation (Asikin et al, 2019, and social order reconfiguration (Sassen, 2010). If design is viewed as means of human desire to reach better future (Dovey, 2010), the practice of architecture can be put to shape, condition, and facilitate social relation and to transmit social meaning for good built forms (Yaneva, 2008(Yaneva, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…The social relationship between the settlement and market is almost without obstacles due to the fact that they are both operated by the same actors while the majority of the night market traders are migrants from outside the area. Therefore, this research was conducted to determine the adaptation strategy for the actors in the Jiung Market Area, especially those in the night market, based on functional, structural, and behavioral aspects [26]. This led to several observations made at the research location with the focus on the space, social conditions, and the relationship between these behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies discussed how the urban form of arrival cities [110] can enhance their capacity for "ingesting immigration, adapting to the on-going changes and successfully responding to the needs of immigrants" [111] (p. 768). For instance, Asikin et al [112] showed that the spatial adaptability/flexibility of some urban form elements in Malang, Indonesia, has enhanced its resilience. This includes, for instance, streets that could be used by migrants as spaces for business and social gatherings/events (e.g., weddings) and dwelling spaces that could be easily adjusted to the lifestyle and needs of the new migrants.…”
Section: Immigration/migrationmentioning
confidence: 99%
“…Most of the research carried out in the reviewed literature focused on the resilienc of the general population, where terms such as society [99,117,[131][132][133][134][135][136][137][138][139][140][141][142][143], city residen [89,91,94,[144][145][146][147], community [77,98,148], ecosystem [137,149] and stakeholders [98,150 were recurrent. Examples of the specified population that was addressed in a few of th reviewed publications include: the low-income population in Accra, Ghana [116]; the M durese migrants in Indonesia [112]; African Americans in the US [115]; the tsunami-a fected communities in Sri Lanka [126]; and the local residents of Nablus, Palestine [120] 3.2.5. Pathways to Urban Resilience Figure 5 shows that 38 out of 106 of the reviewed publications focused on the adap ability pathway to resilience, 33 focused on persistence, 18 did not take an explicit positio (or are unclear), nine discussed a combination of pathways and eight focused on tran formability.…”
Section: Resilience For Whom?mentioning
confidence: 99%